2021
DOI: 10.1590/1516-3180.2020.0420.r2.04022021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of participation level and physical activity on eating behavior and disordered eating symptoms in the Brazilian version of the New Moves intervention: data from a cluster randomized controlled trial

Abstract: BACKGROUND: Childhood and adolescent obesity is a worldwide public health concern. The New Moves program aims to change eating behavior (EB) and physical activity (PA). OBJECTIVE: To evaluate the effectiveness of an intervention and predictors of better outcomes relating to EB and PA levels. DESIGN AND SETTING: Secondary data from a cluster randomized controlled trial in 10 public schools in São Paulo, Brazil. METHODS: 270 female adolescents, aged 12 to 14 years, were analyzed. Participation levels were catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The integrated Brazilian version of the “New Moves” (Dunker & Claudino, 2018) also uses this approach with adolescent girls, with sessions based on nutrition, social support, and physical activity. Although the researchers did not find significant changes for ED risk factors, in a secondary analysis Dunker et al (2021) found that girls with less body image dissatisfaction reported higher daily physical activity levels. Therefore, the authors suggest that engagement in physical activity could be a protective factor against body dissatisfaction, given that it has been inversely associated with several risk factors for EDs and other psychological benefits.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The integrated Brazilian version of the “New Moves” (Dunker & Claudino, 2018) also uses this approach with adolescent girls, with sessions based on nutrition, social support, and physical activity. Although the researchers did not find significant changes for ED risk factors, in a secondary analysis Dunker et al (2021) found that girls with less body image dissatisfaction reported higher daily physical activity levels. Therefore, the authors suggest that engagement in physical activity could be a protective factor against body dissatisfaction, given that it has been inversely associated with several risk factors for EDs and other psychological benefits.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, although the effects of integrative prevention on ED risk factors are promising, only two studies (Castillo et al, 2016, 2019) found the desired effects on body dissatisfaction and disordered eating risk behaviors, with effect sizes from small to medium (see Table 1). Two studies did not found significant effects for these measures, but had a small to medium effect size for physical activity practice (Dunker et al, 2021; Leme et al, 2019). Given these results, further research is strongly recommended because integrative prevention programs may be more cost‐effective, reducing the costs related to the development of two separate prevention programs and avoiding the iatrogenic effects of conflicting messages from obesity and ED‐only prevention programs (Ferrari, 2015; Leme et al, 2019; Sánchez‐Carracedo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our data also showed that having obesity tripled the chances of a higher score on the disordered eating scale. Silveira, cited by Dunker et al (2021), states that “[. .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of obesity has been dramatically increasing in the country, with 12% of the youth population, as well as 20% of adults and 21% of older adults being considered obese in Brazil ( 43 , 44 ). In large part, this scenario is due to sedentary lifestyles ( 45 ). Physical inactivity, a preeminent behavioral risk factor for chronic diseases and early mortality, is one of the most prevalent unhealthy behaviors in Brazilians ( 46 , 47 ).…”
Section: Introductionmentioning
confidence: 99%